There is no Plan B for dealing with the climate crisis. (3rd September 2019) - Pierrehumbert, Raymond
ABSTRACT: To halt global warming, the emission of carbon dioxide into the atmosphere by human activities such as fossil fuel burning, cement production, and deforestation needs to be brought all the way to zero. The longer it takes to do so, the hotter the world will get. Lack of progress towards decarbonization has created justifiable panic about the climate crisis. This has led to an intensified interest in technological climate interventions that involve increasing the reflection of sunlight to space by injecting substances into the stratosphere which lead to the formation of highly reflective particles. When first suggested, such albedo modification schemes were introduced as a "Plan B, " in case the world economy fails to decarbonize, and this scenario has dominated much of the public perception of albedo modification as a savior waiting in the wings to protect the world against massive climate change arising from a failure to decarbonize. But because of the mismatch between the millennial persistence time of carbon dioxide and the sub-decadal persistence of stratospheric particles, albedo modification can never safely play more than a very minor role in the portfolio of solutions. There is simply no substitute for decarbonization.